PERANAN KOPERASI MITRA SEHATI DALAM MENINGKATKAN EKONOMI RAKYAT PADA RUKUN WARGA (RW)14 KELURAHAN SAIL - Ristiliana (P3M STKIP 'Aisyiyah Riau, 2016)
This research is a qualitative research which clearly describes the object. This study aims to determine the role of the Mitra Sehati cooperative in improving the people's economy in Rukun Warga 14 Kelurahan Sail, Tenayan Raya District, Pekanbaru City. The subjects in this study were Mitra Sehati Cooperative at the level of Rukun Warga 14 Kelurahan Sail, Tenayan Raya District, Pekanbaru City. While the object to be researched and become the focus of the main problem in this study is the role of cooperatives in improving the people's economy in Rukun Warga 14 Kelurahan Sail, Tenayan Raya District, Pekanbaru City. The data in this study were taken through several techniques including literary techniques, observation and documentation. Furthermore, the data will be processed and analyzed in a descriptive qualitative manner by pouring it in the form of a complete and detailed description or description or report until finally making a conclusion to be presented as a research result. The research that the authors conducted ultimately resulted in the conclusion that the role of the Mitra Sehati cooperative was more focused on efforts to improve the community's economy, especially the people's economy through the currently developing creative economy, through the following activity categories: 1). Savings and loan unit activities and 2). Procurement of creative economic activities for members and society